Omega-3 Fatty Acids in Thai Vegetables and Freshwater Algae - Phuseerit, Onanong (Food Agricultural Sciences and Technology, 2020)
The aim of this study was to analyze polyunsaturated fatty acid (PUFA) composition in seventeen Thai vegetables, including six species of aquicolous, two freshwater algae, and nine terricolous species. For each sample, palmitic acid, linoleic acid and alpha-linolenic acid (18:3n-3) were the main fatty acids, which constituted nearly 90% of the total fatty acid composition of leaf tissues. The concentration ranges were 5.9 to 310 mg/100g, 3 to 235 mg/100g, 2 to 227 mg/100g, respectively. Green algae contained high level of C18 PUFA and low level of C20 PUFA. The algae and terricolous samples had ratios of n-6/n-3 ranged from 0.6 in Tao num to 2.0 in Phai, while aquicolous vegetable samples had a greater variation being ranged from 0.3 in Krached to 6.3 in Koon. Our findings on the fatty acid profile of vegetable showed n-3 fatty acid and ratio of n-6/n-3 might be of great nutritional interest.